Forming high transmittance GaSnO/Ag/GaSnO conducting electrodes for optoelectronic devices. Issue 18 (15th December 2020) - Kim, Jong-Ho; Cho, Jin-Woo; Kim, Su-Kyung; Kim, Jae-Ho; Kim, Sun-Kyung; Seong, Tae-Yeon
Abstract: We report on the development of high-performance transparent conducting GaSnO (GTO)/Ag/GTO multilayer electrodes for display applications. The optical and electrical characteristics of the GTO/Ag/GTO multilayers were investigated as functions of GTO layer ( d GTO ) and Ag layer ( d Ag ) thicknesses. With increasing d GTO from 10 to 50 nm, the sheet resistance slightly increased from 3.83 to 4.81 Ω/sq, the carrier concentration decreased from 4.76 × 10 22 to 1.12 × 10 22 cm −3, and the mobility (μ) slightly changed from 10.7 to 10.3 cm 2 /V. The 40 nm-thick GTO-based multilayer exhibited the mean transmittance ( T av ) of 91.6% and had the Haacke's figure of merit (FOM) of 87.84 × 10 −3 Ω −1 . The μ value increased from 7.97 to 11.67 cm 2 /V and sheet resistance varied from 7.81 to 3.47 Ω/sq as increasing d Ag from 9 to 15 nm. The T av of the GTO (40 nm)/Ag/GTO (40 nm) samples decreased from 94.5% to 84.9% with increasing dAg . The optical bandgaps of the GTO and GTO/Ag/GTO (40 nm/12 nm/40 nm) films were estimated to be 4.06 and 3.94 eV, respectively. Finite-difference time-domain calculations were conducted to explain the d Ag and d GTO dependent transmittance of the GTO/Ag/GTO samples. With the phasor analyses, the d GTO dependence of the transmittance of GTO/Ag (12 nm)/GTO multilayers is described and discussed. Furthermore, the optical and electrical features of the optimal GTO/Ag/GTO (40 nm/12 nm/40 nm) electrode are compared with those of sputter-deposited 92 nm-thick indium tin oxide (ITO) films.